Hapten Design and Monoclonal Antibody to Fluoroacetamide, a Small and Highly Toxic Chemical - Ling Yang; Xiya Zhang; Dongshuai Shen; Xuezhi Yu; Yuan Li; Kai Wen; Jianzhong Shen; Zhanhui Wang (Biomolecules, 2020)
Fluoroacetamide (FAM) is a small (77 Da) and highly toxic chemical, formerly used as a rodenticide and potentially as a poison by terrorists. Poisoning with FAM has occurred in humans, but few reliably rapid detection methods and antidotes have been reported. Therefore, producing a specific antibody to FAM is not only critical for the development of a fast diagnostic but also a potential treatment. However, achieving this goal is a great challenge, mainly due to the very low molecular weight of FAM. Here, we design two groups of FAM haptens for the first time, maximally exposing the fluorine or amino groups, with the aid of linear aliphatic or phenyl-contained spacer arms. Interestingly, whereas the hapten with fluorine at the far end of the hapten did not induce an antibody response to FAM, the hapten with an amino group at the far end and phenyl-contained spacer arm triggered a significantly specific antibody response. Finally, a monoclonal antibody (mAb) named 5D11 was successfully obtained with an IC50 value of 97 μg mL−1 and negligible cross-reactivities to the other nine functional and structural analogs.